USE OF INTERACTIVE EDUCATIONAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Adhamjonov Muhammadali (Journal of new century innovations, 2023)
Abstract: the article discusses educational technologies used in the process of learning foreign languages and their role and importance, and the main strategy of education is a student-oriented approach, which is at the center of the educational process. sets the child's personality, abilities, inclinations and needs. All this can be done on the basis of new educational technologies. Modern interactive pedagogical technologies (IPT) include the following: dialogic communication, critical thinking, problem solving, decision-making skills are highlighted.